Microsatellite instability and sex differences in resectable gastric cancer – A pooled analysis of three European cohorts. (September 2022) - Quaas, Alexander; Biesma, Hedde D.; Wagner, Anna D.; Verheij, Marcel; van Berge Henegouwen, Mark I.; Schoemig-Markiefka, Birgid; Pamuk, Aylin; Zander, Thomas; Siemanowski, Janna; Sikorska, Karolina; Egthuijsen, Jacqueline M.P.; Meershoek-Klein Kranenbarg, Elma M.; et al.
Abstract: Objective: Biological sex differences in cancer are increasingly acknowledged. Here, we examined these differences in clinicopathological characteristics and survival in microsatellite instability (MSI)-high and microsatellite stable (MSS) gastric cancer (GC). Design: We analysed MSI status by polymerase chain reaction (PCR) and/or mismatch repair (MMR) status by immunohistochemistry in a pooled analysis of individual patient data from one retrospective cohort from Cologne, and the randomised phase III clinical trials D1/D2 and CRITICS. All patients had resectable adenocarcinoma of the stomach and/or gastro-oesophageal junction. Patients were treated with either surgery only or perioperative chemo(radio)therapy. Results: MSI and/or MMR analyses on 1307 tumours resulted in 1192 (91.2%) MSS and/or MMR proficient (MMRP) [median age, 65 years; 759 males (63.7%); 619 treated with surgery only (51.9%)], and 115 (8.8%) MSI-high [median age, 69 years; 67 males (58.3%); 76 treated with surgery only (66.1%)] GC cases. Males had shorter overall survival (OS) than female MSI-high GC (5-year OS 34.7% vs. 69.7%; hazard ratio (HR) 2.68, 95%CI 1.60 to 4.49; p < 0.001). Females with MSI-high had longer OS than those with MSS/MMRP GC (HR 0.61, 95%CI 0.41 to 0.92; p = 0.02). Males with MSI-high did not have longer OS than those with MSS/MMRP GC (HR 1.26, 95%CI 0.94 to 1.69; p = 0.12). Conclusions: MSI-high GC males had a significantly worse prognosis compared to their female counterparts in three independent cohorts. In addition, the favourable prognostic value of MSI was only seen in females and not in males. These observations emphasise the need to consider sex differences in prognosis and treatment effects in oncology. Clinical trial registration: The CRITICS trial is registered at ClinicalTrials.gov, number NCT00407186; EudraCT, number 2006-004130-32; and CKTO, 2006-02. Highlights: MSI-high gastric cancer males have repeatedly shorter overall survival than females. These survival differences are irrespective of treatment modality in three independent cohorts. MSI-high is only a prognostic factor in female gastric cancer patients, not in males. Sex differences in MSI-high gastric cancer should factor into trial design.